Does early intervention help the unemployed youth? - Kenneth Carling; Laura Larsson (Institute for Labour Market Policy Evaluation (IFAU), 2002)
This paper evaluates a measure targeted at unemployed individuals aged 20-24. The main purpose of the measure is to prevent long-term unemployment by guaranteeing an assignment to some labor market program within 100 days of unemployment. Municipalities voluntarily agree to offer the guarantee. To identify the effect of the measure, we use three conditions: The guarantee covers individuals aged 24 but not 25, one fifth of the municipalities does not provide the guarantee, and the guarantee existed in 1998 but not in 1997. We find no evidence that the measure did significantly improve the future labor market situation of the youth, which suggests that early intervention in the unemployment spell is not important.
Keywords: C14; J64; J68; 330; Guarantee; program evaluation; regression-discontinuity design